PREDICTION OF MINI STUDENT ORAL CASE ANALYSIS TEST AND MINI OBJECTIVE STRUCTURED CLINICAL EXAMINATION WITH THE NATIONAL DOCTOR PROFESSIONAL COMPETENCY TEST IN INDONESIA - Syafruddin, Amir; Permatasari, Tria Astika Endah; Ramadhan, Anwar Ilmar (International Journal of Psychosocial Rehabilitation, 2020)
The national competency test for doctor’s professionalism competencies is an indicator of the doctor’s expertise. The study aimed to analyse Association between Mini Student Oral Case Analysis (SOCA) Test and Mini Objective Structured Clinical Examination (OSCE) with The National Doctor Professional Competency Test. The research method is experimental use a cross-sectional study was conducted in 2019 among 70 students of the medical study Program in Universitas Muhammadiyah Jakarta who were taken the second block. Data was collecting using standardized test instruments based on Indonesian professional medical organizations. Results showed there is no relationship between the results of the mini SOCA test with the results of the National CBT (UKMPPD). There are only 1 of 5 stations that are significantly related to the national OSCE test (Humerus Fracture Station). Conclusion for this study are the mini SOCA and OSCE tests have not been optimal in assessing early national doctor professional student competency test. The mini OSCA and OSCE tests have not been optimal in assessing early national doctor professional student competency test.